System kwot mlecznych a możliwości rozwoju gospodarstw rolnych na Dolnym Śląsku - Tratwal-Uglis, Natalia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of the paper is defining what possibilities of production and economic the as well as organizational are standing in front of the farms dealing with milk production in Lower Silesia after the introduction of the milk system of quotas. The study contains first results of investigations concerning the influence of the milk system of quotas on the transformations in agricultural farms. There was undertaken also trial of detection factors which influenced the height of income from the sale of milk. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 223-229